ANALYSIS OF CASH FLOWS SME’s RAJUT IN KENDALSARI, TULUSREJO, MALANG CITY - Chalimatuz Sa'diyah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
Increasing cash balance is an effort made by SME’s in its operational activities. Cash that is managed optimally can reduce excess cash so that SME’s can maximize profits. There are various ways that SME’s can implement to increase their cash balance, namely by maintaining the cash balance to be optimal and holding back cash that is incurred so as not to overdo it. To achieve this goal, SME’s must improve cash management and SME’s are expected to improve their financial performance. Things that must be avoided in carrying out business activities that can hinder in achieving the goals of SME’s are there are non-rotating cash that settles on cash. Cash that has no turnover can reduce the profits that should be obtained, so that excess cash does not fail and can be used to buy investment so that it provides more benefits to SME’s. This study aims to be able to know and understand the condition of the cash balance and to know and understand the formation of an optimal cash balance, as well as knowing the adequacy of MSME cash flows in Kendalsari, Malang City. This type of research uses case studies, namely research using secondary data. Secondary data used in this study is the history of the establishment of SME’s, MSME financial data, and information on product intricacies. The data analysis technique in this study is to use the Orr Miller Model calculation with the aim to be able to find out the Optimal Cash Balance in SME’s. The results of the study indicate the lower limit of cash availability for SME’s in order to optimize financial performance of Rp. 107,123. Whereas the upper limit of cash should be Rp. 321,396. And the results of the cash flow adequacy ratio show a value of 1.614. Thus the results of this study can be used as a reference for SME’s in conducting cash management. Cash optimization is used to maintain cash so as not to experience shortcomings or excess in carrying out its operational activities so that SME’s can maximize their financial performance. A ratio of 1 indicates that SME’s can cover cash needs without the need to obtain external funding.